Analysis of Amil Zakat Institution Performance Using the Balanced Scorecard Method (Case study in BAZNAS Sragen) - Khadijah, Siti; Afif, Mufti (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2018)
The zakat funds collection, infaq and shadaqah movement in Sragen Regency was formally implemented by the Zakat Infaq and Shadaqah Agency (BAZIS) which was established on May 27, 1991. By the issuance of Law No. 38 of 1999 concerning  Management of  Zakat, it was changed to the National Zakat Agency ( BAZNAS). Amil Zakat Agency (BAZ) Sragen has a number of special programs in introducing zakat to the community. Finally they were  able to collect zakat funds of around Rp. 250 million per month. The zakat funds which are collected at the Sragen BAZ mostly come from civil servants, the TNI and the National Police. However, this program has not been optimal yet, zakat funds absorbed only around Rp. 2 billion per year from the potential of Rp. 7 billion. Therefore, performance measurement  is one of the important factors in companies and institutions to evaluate work results from the past period.This research uses the Balance Scorecard paradigm / perspective, namely measurement using four perspectives; Finance, Customers, Internal Business, Learning and Growth. The method used is descriptive explorative qualitative method. Data was collected by interview, questionnaire and documentation.The results showed that the performance of BAZNAS of Sragen Regency was "Good". The results of the average score of the performance appraisal of BAZNAS in Sragen Regency were 6: 8 = 0.75 which is "Good".